Palladium-Catalyzed C–P Cross-Coupling between (Het)aryl Halides and Secondary Phosphine Oxides - Zakirova, Gladis G.; Mladentsev, Dmitrii Yu.; Borisova, Nataliya E. (Synthesis, 2019)
An efficient procedure for C–P bond formation via the palladium-catalyzed [Pd(OAc)2/dppf/Cs2CO3] reaction between dichloroheterocycles and secondary phosphine oxides was developed. The steric and electronic properties of substituents were varied to establish the scope and limitations of the method developed. By applying these conditions, a variety of new heterocyclic compounds bearing two tertiary phosphine oxides were successfully synthesized in moderate to excellent yields. After adjustments to the reaction conditions [Pd(OAc)2/dippf/t-BuOK], cross-coupling of secondary phosphine oxides with bulky (secondary or tertiary alkyl) substituents on the phosphorus atom was achieved. Extension of the methodology to monohalohetarenes and monohaloarenes was successfully carried out; once again, the steric and electronic properties of the halides were varied widely. The desired reaction occurred in all cases studied, giving high to excellent yields of product regardless of the nature and positions of substituents.
Keywords: cross-coupling; palladium; phosphine oxides; heterocycles; homogeneous catalysis